2021
DOI: 10.1177/08902070211056901
|View full text |Cite
|
Sign up to set email alerts
|

On the Construct-Related Validity of Implicit Trait Policies

Abstract: In response to recent calls to incorporate Implicit Trait Policies (ITPs) into personality research, the current study examined the construct-related validity of ITP measures. ITPs are defined as implicit beliefs about the effectiveness of behaviors that reflect a certain trait. They are assessed by utilizing the methodology of Situational Judgment Tests. We empirically examined ( N = 339) several underlying key assumptions of ITP theory, including trait-specificity, the relation to personality traits, their c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Two recent studies took a closer look at key positions of the debate about the underlying processes of SJT performance. First, Freudenstein et al (2023) demonstrated that typical operationalizations of SJTs are not in line with the conceptualization as measures of general domain knowledge. Specifically, results showed that reliable variance in SJT scores is to a larger degree test‐specific rather than context‐independent, even when SJTs measured the same construct.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Two recent studies took a closer look at key positions of the debate about the underlying processes of SJT performance. First, Freudenstein et al (2023) demonstrated that typical operationalizations of SJTs are not in line with the conceptualization as measures of general domain knowledge. Specifically, results showed that reliable variance in SJT scores is to a larger degree test‐specific rather than context‐independent, even when SJTs measured the same construct.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Second, SJTs represent a collection of methods rather than a specific assessment of definite constructs (Freudenstein et al, 2021; Lievens, Peeters, et al, 2008). Different SJTs vary in their response medium, response format, instruction format, scoring method, and more (Campion et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Second, SJTs represent a collection of methods rather than a specific assessment of definite constructs (Freudenstein et al, 2021;Lievens, Peeters, et al, 2008) SJTs vary in their response medium, response format, instruction format, scoring method, and more (Campion et al, 2014). The common core of most SJTs is the inclusion of a work-related situation description and the focus on the prediction of external criteria such as job performance (Christian et al, 2010;Corstjens et al, 2017) Motowidlo, 2016).…”
Section: Standardized State Assessment and Situational Judgment Testsmentioning
confidence: 99%
“…Traditionally, an ITP is validated by observing the correlation between the trait dimension (e.g., cultural empathy) and the effectiveness of the ITP of said trait dimension (e.g., cultural empathy ITP) ( Motowidlo et al, 2006 ). This correlation is called the saturation of the ITP, which is not always a very strong one ( Freudenstein et al, 2023 ). As a consequence, some accounts in literature have criticized this traditional approach, clearly stating that the variance of an ITP over individuals is not determined by personality alone, but can also include elements like experience, attitudes, motivation and learning ( Oostrom et al, 2012 ; Lievens and Motowidlo, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Instruments that leave out one or more known dimensions of more broad theoretical concepts (e.g., the Big Five of human personality) can endanger the validity of correlation and regression estimates through the omitted variable problem, as the estimated relations are prone to bias (i.e., in the present research’s case an underestimation of saturation) by leaving important elements (e.g., one or more personality dimensions or elements of experience, attitudes, motivation, and learning) out of the equation ( Sackett et al, 2003 ). As a consequence, there are already accounts in literature that disavow the (single) trait specificity of the ITP construct ( Freudenstein et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%